IDENTIFYING THE CRITICAL FACTORS OF STUDENTS’ DIFFICULTY UNDERSTANDING THE CONCEPT OF LOGARITHMS - Ariyani Muljo; Budi Irwansyah; Wanda Darmawan; Juhendrifansyah; Ira Keumalasari (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Logarithms are one of the mathematics lesson materials in the algebra aspect which provide many benefits in everyday life. Despite the many benefits associated with logarithms, most students think that logarithms are something difficult and not worth learning. This research aims to determine important factors in students' difficulties in understanding the concept of logarithms. The samples were 99 class X students from three public high schools in Aceh Tamiang Regency. Data was obtained using a logarithm material diagnostic test instrument based on aspects of logarithms as an object, process, function, and contextual problems. From these four aspects, we identified 17 variables that caused students difficulty in understanding the concept of logarithms. The research results show that there are five main factors that cause students difficulties in understanding the concept of logarithms. These factors are: (a) connecting square roots with logarithms, (b) connecting logarithmic and exponential functions as inverses, (c) rules of logarithmic notation, (d) logarithmic graphs, and (e) simplifying logarithmic expressions